Relationship between gestational risk and type of delivery in high risk pregnancy - Marcos Benatti Antunes; Robson Marcelo Rossi; Sandra Marisa Pelloso (SciELO, 2020)
Abstract Objective: To analyze the association between gestational risk factors and type of delivery in high-risk pregnancies. Method: A cross-sectional epidemiological study involving a retrospective analysis of secondary data from 4,293 medical records of high-risk pregnant women. The primary outcome was composed of risks associated with cesarean delivery and spontaneous abortion compared with normal delivery. Results: There were 3,448 women analyzed in the study. The primary outcome rates were cesarean delivery (72.8%), spontaneous abortion (0.9%) versus vaginal delivery (26.2%). Common risk factors for cesarean delivery and spontaneous abortion were age ≥35 years (OR = 1.4; 95% CI 1.1-1.7 / OR = 11.5; 95% CI 4.2-31.0), evangelical religion (OR = 1.4; 95% CI 1.2-1.7 / OR = 2.6; 95% CI 1.0-6.7), high blood pressure (OR = 1.4; 95% CI 1.1-1.8 / OR = 74.9; 95% CI 13.7-410.2) and twinning (OR = 3.1; 95% CI 1.9-5.0 / OR = 68.6, 95% CI 9.7-487.7). Conclusion: Identifying the relationship of gestational risks with the type of delivery and abortion can contribute to developing strategies and assist in planning actions in women's healthcare networks, developing specific and individualized lines of care for each gestational risk.